Investigating antecedents of plagiarism using extended theory of planned behavior - Uzun, Ahmet Murat; Kilis, Selcan (Computers and education, 2020)
Plagiarism has received considerable attention over the past two decades. Exploring the predictors of this type of academic misconduct can support stakeholders when confronting and managing the incidents of plagiarism. Using an extension of the Theory of Planned Behavior (TPB) framework, this study aims to understand the antecedents of plagiarism. In the study, the influence of new variables such as moral obligation and past behavior were tested along with more familiar TPB constructs. Moreover, the variable of perceived behavioral control was substituted with the Information and Communication Technologies (ICT) literacy variable, which is measured using Internet, computer and information literacy. Adopting a cross-sectional survey design, the data were collected from 588 university students and analyzed using partial least squares structural equation modeling. The results demonstrated that attitude, information literacy, moral obligation and past behavior were significant predictors of behavior intention to engage in plagiarism, whilst subjective norms, Internet literacy and computer literacy were not. The study concluded that the most appropriate way to combat plagiarism is through pedagogy. Offering more courses to university students on the subjects of ethics, morality and literacy is therefore highly recommended. •Plagiarism antecedents explored through extended Theory of Planned Behavior.•ICT literacy regarded as a proxy for perceived behavioral control.•Among ICT constructs, only information literacy predicted intention.•Past behavior and moral obligation were the strongest determinants of intention.•Attitude and information literacy had small yet similar effects on intention.